Tailgates, Traffic, Police Militarization, and the Shadow of the Next School Shooting: Campus Police and the 1033 Program - Corradi, Andrea (American journal of criminal justice, 2025)
With rising concerns surrounding police misuse of power and necessary responses to major crimes on college and university campuses, it is important to examine the potential militarization of campus police departments. While the militarization of non-campus police receives significant attention, there are distinct differences between these departments and police departments on campuses. To help shed light on militarization on college campuses, we rely on data from the Department of Defense (DOD) 1033 Program, which provides police departments an opportunity to request surplus military equipment. This request process includes justifications for why they need the item, allowing insight into the perceptions and duties of campus police officers. Using constructivist grounded theory, we qualitatively code 1,613 justifications by college and university police departments in the United States. Results suggest that while campus police departments have many commonalities with standard police departments, they also face unique challenges that they use DOD material to meet including the consistent presence of crowds, unique environmental contexts, and the ever-present risk of active shooters.